Evaluation of Different Root Canal Filling Techniques in Severely Curved Canals by Micro-computed Tomography - Alim, Betül Aycan; UYSAL, BETÜL AYCAN; Garıp Berker, Yıldız (My University, 2019)
AimTo fill the severely curved root canals with different filling techniques and to compare these techniques using micro-computed tomography (micro-CT).Materials and methodsSixty extracted mandibular first molars (degree of root canal curvature > 25°) were selected. All samples were divided into four groups and filled with one of the following techniques: lateral condensation, single-cone, continuous-wave obturation, and core carrier. After they were scanned by micro-CT, the total area, filled area and void area of the root canal were calculated. The Mann–Whitney U and Kruskal–Wallis tests were used for statistical analysis (p<0.05).ResultsIt was shown that significantly more filling material was used in the lateral condensation and core carrier technique groups at 2 and 5 mm than in the single-cone and continuous-wave obturation technique groups (p<0.05). It was observed no statistically significant difference at 8 mm (p > 0.05).ConclusionNo technique could completely fill in root canal. Regarding the coronal part, all techniques can be used for more effective filling as long as a good condensation is achieved. The use of a plugger with an optimal size according to the localisation of root canal curvature and the choice of a heat-resistant root canal sealer affects the success of the treatment in the thermoplastic techniques.